The rough guide to Irish folk (Music rough guide, ,, 2009)
Description Not Provided
Crooked Jack (Seamie O'Dowd) (3:58) --, Pota mó fataí (Róosín Elsafty) (2:56) --, The yellow barber ; Gold rush (Chris Newman) (3:16) --, The rich Irish lady (Patrick Street) (5:06) --, Tripin' (Luke Ward) (4:55) --, Town of Athlone (Karen Casey) (2:50) --, The flower of Kilkenny (Robbie O'Connell) (3:54) --, Dan Murphy's ; Tom Barrett's ; Tarmon's cross ; Upperchurch polka (Four Men and a Dog) (4:14) --, Beauty deas an oileáin (Julie Fowlis) (4:07) --, The Spoons murder (Con ÓDrisceoil) (5:12) --, Jimmy mó mhíle stór (Cara Dillon) (3:56) --, Elizabeth Kelly's favourite ; Follow me down to Limerick (Catherine McEvoy) (4:14) --, The men that God made mad ; Entrada de l'Angustura (Graham Dunne) (3:57) --, High road to Linton ; The humours of Newcastle (Brendan Hendry) (3:00) --, St. Patrick was a gentleman (Rattle the Boards) (3:27) --, The Lochaber badger ; The road to Corrandulla (Michael McGoldrick) (4:35) --, The rising of the moon (Seán Tyrell) (6:04) --, Love is pleasing (4:59) ; Dulnavin green (4:35) ; Johnny I hardly knew ye (4:23) ; Black is the colour (5:02) ; Town of Athlone (4:21) ; Maidin luan chincíse (4:21) ; The fiddle and the drum (4:38) ; Erin's lovely home (5:38) ; Ae fond kiss (4:06) ; I once loved a lass (5:20) (Karan Casey).